How Academic Experiences and Educational Aspirations Relate to Well-Being and Health among Indigenous Sami Youth in Northern Norway. A Qualitative Approach - Nystad, Kristine; Ingstad, Benedicte; Spein, Anna Rita (Umeå University, 2020)
Source at http://www.jns.org.umu.se/index.htm . Increasingly, education occupies the lives of Indigenous adolescents worldwide. This qualitative study is part of the project “Circumpolar Indigenous Pathways to Adulthood” (CIPA), where the overall aim was to identify young people’s stressors in five circumpolar sites, and the resilience processes that safeguard transition into adulthood (Allen et al. 2014). The present study explores the everyday lives of young Sami in Northern Norway regarding educational demands and plans, related challenges and stressors and their impact on well-being, health and cultural continuity. Semi-structured interviews were conducted in 2010 (N=22) with reindeer husbandry affiliation (RH: 11) and non-reindeer husbandry affiliation (NRH: 11) adolescents, aged 13–19 (females: 12). School well-being was divided into educational factors (culture-based teaching, e.g. Sami handicraft and outdoor practices), environmental factors (e.g. school canteen) and social factors (e.g. caring teachers), while challenges and stressors were educational (e.g. getting good marks), environmental (e.g. noise) and social (e.g. bullying). Lower secondary school pupils called for more tradition-based teaching. Educational aspirations were highest among females and NRH males. RH males generally planned to continue their traditional lifestyle and showed the strongest place attachment. We also address the maintenance of cultural continuity, which is important for the well-being and health of Indigenous youth.